Effects of Brisk Walking on Plasma Lipoprotein(a), Total Antioxidant Status, Aerobic Fitness, Percent Body Fat, Waist Circumference and Resting Blood Pressure in Overweight and Obese Females - CK, Chen; NS, Kamarul Hisham; NA, Jeffri (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Obesity is a major public health challenge in many nations including Malaysia. Physical activity has been shown to be a modifiable determinant of obesity and non-communicable diseases. The objective of this study is to investigate the effects of 6 weeks of brisk walking on plasma lipoprotein(a), total antioxidant status, percent body fat, aerobic fitness, waist circumference and resting blood pressure in overweight and obese females. MATERIALS AND METHODS: Thirty-eight females (Age: 23.2 ± 3.9 years BMI: 28.8 ± 4.5 kg.m-2) were randomly assigned into 2 groups: control (C) and brisk walking (BW) groups. Pre- and post-tests were carried out to measure participants’ anthropometric measurements, aerobic fitness, resting blood pressure and blood sample for lipoprotein(a) and total antioxidant levels. Participants in BW group performed the brisk walking exercise, 3 sessions per week for 6 weeks. Participants in C group maintained their sedentary lifestyle and refrained from any other training programme. Results: After 6 weeks of intervention, plasma lipoprotein(a) level was significantly reduced in both BW and C groups. There were also significant reductions in waist circumference, percent body fat and resting blood pressure in BW group. However, there were no significant differences in total antioxidant status and aerobic fitness after the brisk walking programme. Conclusion: 6 weeks of brisk walking programme reduces plasma lipoprotein(a), percent body fat, waist circumference and resting blood pressure in overweight and obese females. Therefore, brisk walking is an appropriate exercise to reduce some of the risk factors for noncommunicable diseases among overweight and obese females.